Melacak asal usul gerakan Paderi di Sumatra Barat - Murodi, 1964- (Jakarta : Logos, 1999)
History of Paderi movement, 19th century Islamic religious and political movement in Sumatera Barat Province.
Includes bibliographical references (p. 135-138) and index.
Keywords: Sumatera Barat (Indonesia) -- History; Indonesia -- History -- Padri War, 1803-1838.